Preventive effect of greater occipital nerve block on patients with episodic migraine: A randomized double‐blind placebo‐controlled clinical trial. (May 2022) - Malekian, Nazila; Bastani, Pouya B; Oveisgharan, Shahram; Nabaei, Ghaemeh; Abdi, Siamak
Abstract: Objective: Since the data regarding the efficacy of greater occipital in episodic migraines are rare, we aimed to examine the efficacy of greater occipital block in the prophylaxis of episodic migraines without aura and compare different injectable drug regimens. Methods: In a randomized, double-blind placebo-controlled trial, adult patients suffering from episodic migraines without aura were randomized to one of the following: triamcinolone, lidocaine, triamcinolone plus lidocaine, and saline. Patients were assessed at baseline, one week, two weeks, and four weeks after the injection for severity and duration of headaches and side effects. Results: Fifty-five patients completed the study. Repeated measures ANOVA indicated that the severity and duration decreased significantly after the greater occipital block (P < 0.001, P = 0.001 respectively) in all four groups. However, there was no difference between groups at any study time points (P > 0.05). In paired sample T-test, only groups 2 and 3 with lidocaine as a part of the injection showed a significant decrease in frequency compared to the baseline (P = 0.002, P = 0.019). Three patients reported side effects with a possible association with triamcinolone. Conclusion: Greater occipital block with a local anesthetic significantly decreases the number of attacks in episodic migraine, whereas no injection was superior to the placebo in regards to the duration and severity of the headaches. Trial Registration Information: Iranian Registry of Clinical Trials (IRCT). Registration number: IRCT2017070334879N1.https://www.irct.ir/trial/26537 .